Fatal Revolutions : Natural History, West Indian Slavery, and the Routes of American Literature - Iannini, Christopher P. (Book collections on Project MUSE., 2012)
Drawing on letters, illustrations, engravings, and neglected manuscripts, this book connects two dramatic transformations in the eighteenth-century Atlantic world - the emergence and growth of the Caribbean plantation system and the rise of natural science. It argues that these transformations were not only deeply interconnected, but that together they established conditions fundamental to the development of a distinctive literary culture in the early Americas.